Cross-Border Related Party Sales, Tax Avoidance, and Tunneling: Regulatory Impacts on Indonesian Manufacturing Companies - Barokah, Zuni; Nindya Sari, Nurma (The Indonesian Journal of Accounting Research, 2024)
This study investigates the influence of a company's tax avoidance on the firms’ related-party transactions. Specifically, it focuses on the specific types of related-party transactions, i.e., related-party sales with foreign affiliates (the cross-border sales of related-party transactions: CB-RPT) and related-party other receivables (RPOR). We further investigate whether the introduction of government regulation concerning transfer pricing “TP Documentation” affects firms’ CB-RPT practices by comparing the results between the pre-and post-period of regulation, i.e., 2012 – 2016 and 2017-2019, respectively. We conducted multiple regression analyses on the manufacturing companies listed on the Indonesia Stock Exchange from 2012 to 2019. Our findings show that tax avoidance has a positive and significant association with both CB-RPT and RPOR in the period preceding the regulation (i.e., 2012-2016), suggesting that companies use the transactions to fulfill tax avoidance strategy and tunnel out the additional resources to their related parties. However, we find no significant impacts of tax avoidance on both CB-RPT and RPOR in the post-period (2017-2019), indicating that companies seem to change their strategy in utilizing transfer pricing for tax avoidance purposes following the enactment of the new regulation.